Quality of medical information determine the quality of diagnosis code - Warsi Maryati; Indriyati Oktaviano Rahayuningrum; Ani Ismayani (International Journal of Public Health Science (IJPHS), 2019)
The accuracy of the diagnosis code has implications for future patient care planning, provision of health services and patient care costs. Therefore, this study has analyzed the influence of the quality of medical information on the quality of the diagnosis code which includes the accuracy, consistency, completeness and timeliness in coding the diagnosis of inpatients at Dr. Moewardi hospital.This was an observational analytic study with a sample of 250 medical records taken using stratified random sampling. Data were analyzed by chi square test. High quality of medical information has a better diagnosis code quality (73.80%) compared to poorly quality of medical information (36.00%). High quality of medical information has a log odds of 1.54 better in the quality of diagnosis code than poorly quality of medical information (b=1.54; 95% CI=0.81-2.27, p<0.001).